The effect of unemployment rate, human development index, gross domestic product against level of poverty in Indonesia - Inda Arfa Syera (Proceedings of AICS - Social Sciences, 2017)
The aim of this paper is to know the effect of the unemployment rate, human development index, and gross domestic product against level of poverty in Indonesia year of 2002-2013. The data used are secondary data obtained from the Central Bureau of Statistics. The data period used is the start year 2002-2013. The data is processed by applying a multiple linier regression analysis. The result is unemployment rate; human development index and gross domestic product have an effect on the level of poverty in Indonesia year of 2002-2013.